2013
DOI: 10.11622/smedj.2013218
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic T wave abnormalities

Abstract: A 61-year-old man was admitted for intermittent chest pain, which lasted for over one week. It worsened on exertion and was associated with diaphoresis. The pain was described as a central squeezing sensation that lasted for about ten minutes and was relieved with rest. Cardiovascular examination of the patient was unremarkable, and he was normotensive at rest.What are the electrocardiographic (ECG) abnormalities seen in Fig. 1?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 2 publications
(2 reference statements)
0
9
0
1
Order By: Relevance
“…During phase 3, there is closure of the calcium channels, while the potassium channels remain open, resulting in rapid loss of positive charge from the cardiomyocytes and restoration of the resting membrane potential (Issa et al 2009). As such, the configuration of the T wave is dependent on the spatial-temporal characteristics of ventricular repolarization (Lin et al 2013). The T-wave in cats can be positive, negative, or biphasic (Tilley & Burtinick 1999).…”
Section: Discussionmentioning
confidence: 99%
“…During phase 3, there is closure of the calcium channels, while the potassium channels remain open, resulting in rapid loss of positive charge from the cardiomyocytes and restoration of the resting membrane potential (Issa et al 2009). As such, the configuration of the T wave is dependent on the spatial-temporal characteristics of ventricular repolarization (Lin et al 2013). The T-wave in cats can be positive, negative, or biphasic (Tilley & Burtinick 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The pattern of values, which was extracted as features (T-amp and T-right slope from lead II, V3, V4, V5, and V6), showed well-known patterns. It is known that the amplitude of T wave is maximal in lead V3 [18]. In addition, T wave in the precordial leads (<10 mm or <1 mV) is usually greater than that in the limb (<5 mm or 0.5 mV) leads [18].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the amplitude of T wave is maximal in lead V3 [18]. In addition, T wave in the precordial leads (<10 mm or <1 mV) is usually greater than that in the limb (<5 mm or 0.5 mV) leads [18]. In our results, only less than 2% in the total patient group (6 in lead II, 5 in lead V3, 5 in lead V4, 1 in lead V5, and 0 in lead V6 among 330 ECGs) and the normal ECG subgroup (2 in lead II, 4 in lead V3, 1 in lead V4, 0 in lead V5, and 0 in lead V6 among 231 normal ECGs) exceeded 0.5 mV in the limb lead or 1 mV in the precordial leads, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…An ECG case series also reports that PE is one of the causes of T wave abnormalities. (11) Another study showed that the most common finding in confirmed massive PE was T wave inversions in the precordial leads with an earlier onset in the more severe cases. (12) This was observed in Case 2.…”
Section: Ecg Featuresmentioning
confidence: 99%